In Vitro and in Vivo Cytotoxic Effects of Chlorella Against Various types of Cancer - R, Ahmad Raus; NS, Adzahar; DF, Basri; ES, Latif; NJ, Sallehudin (IIUM Medical Journal Malaysia, 2021)
Chlorella is one of the microalgae that had been studied intensively owing to its rapid growth and easily cultured at a large scale compared to other microalgae and valuable nutrient compositions. Numerous studies have observed that Chlorella possess various health benefit including antioxidant, anti-cholesterol, anti-inflammatory, and antiproliferative effect against many types of cancer. In this review paper, the effects of various Chlorella species against cancer cells and animal induced cancer are discussed and an overview on Chlorella is briefed. The Chlorella deleterious effect on cancer through various mechanisms such as enhancement of immune system and apoptosis; improving lipid peroxidation; synthesis and expression of the protein-degrading matrix; and preventing the formation of new blood vessels are elaborated as well. Based on the findings of many studies reported in this article, it can be suggested that Chlorella has the potential in supporting cancer therapy and may develop to become an anti-cancer agent.